City Logistics 3 : Towards Sustainable and Liveable Cities. - Taniguchi, Eiichi (John Wiley & Sons, Incorporated, 2018)
This volume of three books presents recent advances in modelling, planning and evaluating city logistics for sustainable and liveable cities based on the application of ICT (Information and Communication Technology) and ITS (Intelligent Transport Systems).